Book Review: Language Curriculum Design - Reskyani, Reskyani; Atmowardoyo, Haryanto (Celebes Journal of Language Studies, 2022)
Today we can see that curriculum design is very important. because this is based on evidence by researchers in his book the curriculum in language teaching is based on Jack C. Richard (2001) while the development of this material for teaching materials is written by Tomlinson (2003). Based on the two books, explains how the curriculum is designed for language learning or education. Thus, this book review is carried out to provide information, and evaluate the contents of the book and also as an opinion on the quality of the book. the presentation of this critical review of the book Nation is to serve as input for readers to provide them with information related to the design of a curriculum. The reviewer classifies into three sessions of fourteen chapters based on the book: two chapters explain the language curriculum design generally that’s chapter one and chapter fourteen, in chapter two until chapter ten, the authors explain the processes of language curriculum design specifically and syllabus and the rest of the chapters provide some aspects that occur in language curriculum design. The sub-points provided in every chapter successfully guide the readers to understand the process of designing a language curriculum. The presentation of every chapter is clear and the content is easy to understand. The summary is given in every chapter successfully becomes a guideline for readers to understand how each topic relates to the previous chapter.